A Secured Fingerprint Authentication System - Islam, Md. Rajibul; Sayeed, Md. Shohel; Samraj, Andrews (Asian Network for Scientific Information (ANSINET), 2008)
This study is a protection analysis of foremost privacy enhanced technologies for biometrics including watermark embedding technique and fixed digit encryption. A biometric authentication system is vulnerable to a mixture of attacks. These attacks are anticipated to either evade the security afforded by the system or to discourage the usual functioning of the system. Here, we briefly review some of the known attacks that can be encountered by a biometric system and some corresponding protection techniques. We explicitly focus on threats designed to extract information about the original biometric data of an individual from the stored data as well as the entire authentication system. We offer a biometric authentication scheme which uses two separate biometric features combined by watermark embedding with fixed digit encryption to obtain a non-unique identifier of the individual, in order to address security and privacy concerns. Moreover, we provide experimental results presenting the performance of the authentication system. In the client-server environment the transformed features and templates travel through insecure communication line like the internet or intranet. Our proposed technique causes security against eavesdropping and replay attacks on the internet or intranet, because the transmitted feature information and the templates are different every time.